2018
DOI: 10.1111/ajt.14924
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual and academic outcomes after pediatric liver transplantation: Relationship with transplant-related factors

Abstract: As survival rates for pediatric liver transplant continue to increase, research attention is turning toward long-term functional consequences, with particular interest in whether medical and transplant-related factors are implicated in neurocognitive outcomes. The relative importance of different factors is unclear, due to a lack of methodological uniformity, inclusion of differing primary diagnoses, varying transplant policies, and organ availability in different jurisdictions. This cross-sectional, single-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 31 publications
1
33
1
Order By: Relevance
“…The SPLIT longitudinal study found that FSIQ was 71‐85 in 29% of those assessed and <70 in 7% . Afshar et al in an Australian cohort of 40 patients assessed at age 6‐16 years found FSIQ of 70‐84 in 25% and of <70 in 7.5% . For VMI and GAC, the average scores in our study were more than one‐half SD of population norms, suggesting that as a group, these children have difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The SPLIT longitudinal study found that FSIQ was 71‐85 in 29% of those assessed and <70 in 7% . Afshar et al in an Australian cohort of 40 patients assessed at age 6‐16 years found FSIQ of 70‐84 in 25% and of <70 in 7.5% . For VMI and GAC, the average scores in our study were more than one‐half SD of population norms, suggesting that as a group, these children have difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we were unable to confirm previous studies that have suggested various but inconsistent predictors of outcomes. 4…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations